Risk considerations for Brazilian tailings dam closure - Ritchie, DG; Baumgardner, Z (Mine Closure 2023: Proceedings of the 16th International Conference on Mine Closure, 2023)
The January 25, 2019 failure of the Corrego de Feijao tailings dam in Brumandinho, Brazil owned by Vale S.A. resulted in 270 lives lost along with significant environmental and cultural heritage impacts. Pursuant to this failure the Public Ministry of the State of Minas Gerais (MPMG) initiated a series of dam safety audits to enhance dam safety oversight and effect change within the Brazilian mining industry, concurrently with the Brazilian National Mining Agency (ANM) issuing legislation in February 2019 requiring the removal or stabilization and decharacterization (deregistration) of all upstream tailings dams. This paper discusses the dam closure risk considerations and experience on various dam safety audits carried out by SLR Consulting (Canada) on behalf of MPMG. The audits involved dams raised by a variety of methods including the upstream method founded on deposited tailings. In general, the focus of the technical audits included geotechnical characterization of the dam and foundation, dam design and construction stewardship, public and worker safety, and emergency preparedness, from the perspectives of both Brazilian regulations and international tailings and dam safety practice. Case studies are presented within three groupings to highlight various experiences: modifications introduced for works that had been carried out prior to commencing the audits, works designed and executed during the audit oversight, and design and planning considerations for closure works that are in progress for high-risk upstream-raised tailings dams. For all cases, the long-term risks, credible failure modes, and operational controls during construction are discussed. The Group 1 case studies highlight the importance of a holistic, long-term risk management perspective. The dam discussed was decharacterized as a mining dam prior to commencing the dam safety audits but was deemed susceptible to credible failure modes including slope instability, erosion, and spillway downcutting. In 2022 the Brazilian national mining agency updated the administration of mining dams to include a minimum of two years of monitoring after completion of the closure works. Notwithstanding, Vale is implementing improvements to the dam as part of their evolving dam safety governance practices in response to audit recommendations. Closure activities for the two dams in Group 2 involved low risk. Closure was planned and successfully completed within the period of the audits. For these dams, design decisions were made after comparing alternative closure scenarios by long-term objectives, constructability, dam safety during construction, and environmental and social considerations. Construction vibration testing was carried out to ensure construction-induced vibrations did not impact adjacent dams. The Group 3 case studies discuss design and planning decisions related to decharacterization of three upstream-raised tailings dams, two of which are at emergency levels. Prior to commencing construction dam breach inundation studies were carried out, emergency preparedness and response plans updated, and citizens in the potential inundation zone were evacuated and/or back-up or emergency containment dams were built. Construction planning included consideration of remotely-operated construction equipment, dam instrumentation (geophones, seismographs and piezometers) to detect construction-induce vibrations that could trigger tailings liquefaction, water management, and planning of staged excavations.
Keywords: tailings liquefaction